Filogeografía del pez loro Sparisoma viride (Bonnaterre, 1788) (Perciformes: Scaridae) en el Gran Caribe - Loera Padilla, Francisco Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
The Greater Caribbean (GC) has been divided into three biogeographic provinces (north, center and south) bounded by differences in salinity, transparency and quantity of nutrients. It has been suggested that these environmental differences play an important role in shaping the distribution and evolution of reef fish within this coastal region, as they can act as barriers to gene flow. Phylogeographic analyzes, population genetics and coalescent methods were performed to examine the evolutionary history of stoplight parrotfish Sparisoma viride and the role of possible environmental barriers in the genetic structure and connectivity of their populations in the Greater Caribbean. Two mitochondrial (d-loop and coxI) and one nuclear (RHO) markers were used. The values of Tajima and Fu F tests were negative and significant, which is associated with events of bottlenecks followed by a population expansion. This demographic increase was dated by the BSP analysis during an interglacial period of the Pleistocene. The stoplight parrotfish presented high haplotypic diversity (Hd) and low nucleotide diversity (?) in the d-loop, while coxI and RHO exhibited low values of genetic diversity. The networks constructed with the three markers did not show evidence of genetic structure in the population, since haplotypes shared between regions and populations were found. The AMOVA found the highest percentage of the variation within the populations and not between the provinces of the GC, indicating a panmictic population of the species throughout the Greater Caribbean. The paired FSTs revealed subtle genetic differences at local scale between some of the populations of the Mexican and South American coasts with respect to Belize, which could be driven by the larval retention caused by the Belize turn.

El Gran Caribe (GC) ha sido dividido en tres provincias biogeográficas (norte, centro y sur) delimitadas por las diferencias en salinidad, transparencia y cantidad de nutrientes. Se ha planteado que estas diferencias ambientales juegan un papel importante en la configuración de la distribución y evolución de los peces arrecifales dentro de esta región costera, ya que pueden fungir como barreras al flujo de genes. Se realizaron análisis filogeográficos, de genética de poblaciones y métodos coalescentes para examinar la historia evolutiva del pez loro Sparisoma viride y el papel de las posibles barreras ambientales en la estructura genética y conectividad de sus poblaciones en el Gran Caribe. Se utilizaron dos marcadores de ADN mitocondrial (d-loop y coxI) y uno nuclear (RHO). Los valores de la D´ de Tajima y F´de Fu fueron negativos y significativos, lo que se asocia con eventos de cuellos de botella seguidos de una expansión poblacional. Este incremento demográfico fue fechado por el análisis BSP durante un período interglaciar del pleistoceno. Sparisoma viride presentó alta diversidad haplotípica (Hd) y baja diversidad nucleotídica (π) en el d-loop, mientras que coxI y RHO exhibieron valores bajos de diversidad genética. Las redes construidas con los tres marcadores no mostraron evidencia de estructura genética en la población, ya que se encontraron haplotipos compartidos entre las regiones y las poblaciones. El AMOVA encontró el mayor porcentaje de la variación dentro de las poblaciones y no entre las provincias del GC, indicando una población panmíctica de la especie a lo largo del Gran Caribe. Las FST pareadas revelaron diferencias genéticas sutiles a escala local entre algunas de las poblaciones de la costa mexicana y sudamericana respecto a Belice, lo que podría ser impulsado por la retención larval ocasionada por el giro de Belice.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FB-M-2018-0381; Opción en ecología y conservación; Provincias biogeográficas; Barreras ambientales; Población panmíctica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1783